The Committee of basin as instrument of democratisation water resources. A Case study: the role of the Committee Basin AcaraÃ â CearÃ - Daniel Sanford Moreira (2014)
This study deals with the experience of the AcaraÃ Basin Committee, the process democratization of the Water Resources Management in AcaraÃ region bathed by the AcaraÃ River, in the State of CearÃ, Brazil. The deployment of AcaraÃ basin committee brought to the local community the opportunity to meet and discuss key aspects of the decentralization and democratization of the State Water Resources Policy Process, provided by laws that now govern the participatory management of water resources both at the state level as federal. Novel experience for most members of the committee makes room for new paradigms in defining the participatory management process to follow, since the decision making run of discussion and deliberation at meetings of the committee members on the basis of management tools. The empowerment and recognition of the AcaraÃ Basin Committee brings the perspective of consolidating space resolution of the State Policy for Water Resources in the region. The aim of this study was to evaluate the advances in water resources of the State of CearÃ, through the Basin Committees policy as an instrument of democratization of water resources in the river basin AcaraÃ. The paper is organized into five chapters. The Introduction deals with the statement of the problem, the scope of work and discusses how the document is organized. The Chapter 2 presents a literature review and legal bases; the Chapter 3 presents the methodology used for the study in question, and describes the Committee of River Basin AcaraÃ; the Chapter 4 presents the results of research; finally, chapter 5 presents conclusions of this research and makes some suggestions of complementary studies.